Angular coefficients of Z bosons produced in pp collisions at $\sqrt{s}$ = 8 TeV and decaying to $μ^+ μ^-$ as a function of transverse momentum and rapidity - CMS collaboration (2178 authors) (2015)
Measurements of the five most significant angular coefficients, A[0] through A[4], for Z bosons produced in pp collisions at $\sqrt{s}$ = 8 TeV and decaying to $μ^+ μ^-$ are presented as a function of the transverse momentum and rapidity of Z boson. The integrated luminosity of the dataset collected with the CMS detector at the LHC corresponds to 19.7 inverse femtobarns. These measurements provide comprehensive information about Z boson production mechanisms, and are compared to QCD predictions at leading order, next-to-leading order, and next-to-next-to-leading order in perturbation theory.